Peran BUMDES dalam Pengembangan Objek Wisata Pantai Di Desa Pitu Kecamatan Tobelo Tengah Kabupaten Halmahera Utara - Tambajong, Junisa Eflian; Tambas, Jane Sulinda; Timban, Jean Fanny Junita (Sam Ratulangi University, 2023)
This research aims to determine the role of BUMDES in raising awareness, capacity and empowering the community in developing beach tourism objects in Pitu Village in Central Tobelo District. The research was carried out over a period of 4 months, namely September to December 2020. Determining the sample in this study used the snowball sampling method. This research uses two types of data, namely primary and secondary data. The data analysis used is descriptive analysis. The results of the research show that the role of BUMDES in raising awareness, capacity and empowering the community in the development of beach tourism objects in Pitu Village in Tobelo Tengah District, it can be concluded (1) Awareness aspect, changing behavior from unwilling to willing, namely increasing village community awareness in maintaining cleanliness and safety of village residential environments and tourist locations. (2) Capacity aspect, increasing the skills of community business actors in managing businesses at the Pitu Beach Tourism location, such as how to make typical Pitu Village food and drinks. (3) Empowerment aspect, increasing business turnover managed by the community at the Pitu Beach Tourism location. Because of the trust of the village government through the BUMDES, the village government provides grants from village funds for business capital.